Intramachine and intermachine variability in transesophageal color doppler images of pulsatile jets: in vitro studies - Fan, Pohoey; Nanda, Navin C.; Anayiotos, Andreas (My University, 1994)
Background: Color Doppler flow mapping is widely used as a marker of severity of valvular regurgitation, and the transesophageal approach has provided high-quality images in patients with poor acoustic windows. However, different instruments produce significantly variable images. Techniques that use jet spatial information to determine the severity of the lesion may need to be derived specifically for the instrument used. Given a lack of standardization of the many commonly used instruments, the goal of this study was to quantify variability between instruments by imaging well-defined jet flow fields created in vitro. Methods and Results: Pulsatile jets were created in vitro using a blood analogue fluid through physiological orifice diameters and imaged from a distal window using six commonly used color Doppler instruments. Transesophageal transducers (5.0 MHz) were used with all instruments studied. Peak jet areas were planimetered and averaged with systematic variations in Nyquist limit, color filter, and sector angle (which produced variations in frame rate). Changes in instrument settings produced significant variation in jet size for all instruments studied. Comparisons within instruments and among instruments were difficult because of preset and ambiguous setting levels. When comparisons were possible between similar settings, variability was dramatic (eg, 57% variability between instruments with very similar Nyquist limits). Conclusions: A lack of standardized color Doppler instrument settings prohibits translation of jet area techniques from one instrument to another. This should be taken into consideration when using different machines for clinical study.
Keywords: Echocardiography; Diagnostic imaging; Image analysis; Transesophageal echocardiography; Algorithms